(untitled) (Journal of the College of Basic Education, 2023)
This study will try to reveal a British personality who contributed in different roles in the realities. history that the Arabian Peninsula in general and the Kingdom of Saudi Arabia went through in particular, in light of the intensification of The Ottoman-British competition for control of the region, as well as the escalation of the struggle between the leaders of the Arabian Peninsula, in the attempt of each party to achieve its objectives at the expense of the other party, while Britain is watching the events closely and is exerting its efforts through its representatives in the Gulf and the Arabian Peninsula, to perpetuate the situation.